SISTEM INFORMASI PENERIMAAN DAN PEMBAGIAN ZAKAT INFAQ SEDEKAH DI BAZIS KECAMATAN CARITA BERBASIS DESKTOP - Agung Sugiarto; Eva Sutihat; Bambang Hudoyono (International Journal Mathla’ul Anwar of Halal Issues, 2022)
The ZIS information system is a system for the administration of all ZIS data of the Carita district, which is managed by the Carita district Bazis. Manually collected data and many errors in data logging and storage, and a high error rate due to the slow influx of ZIS data from all villages in the Carita subdistrict. The method of applied research is a qualitative method that emphasizes the importance, justification and definition of a specific situation, which leads the author to create an application program, the production process of which is Microsoft Visual Basic 6.0, Microsoft Access 2010 and Qrystalreport 8 for the report used . The application program consists of several tables that are used to create Muzzaki data, transaction data and sales data (Mustahik). After entering the data, it creates a report like Muzzaki Reports, Transaction Reports and Sales Reports.This data is processed by this application with input muzzaki, transaction data, sales data (mustahik) and can also store this data in the application.